255 Situation analysis on child maltreatment prevention in several South East European countries. (1st September 2016) - Peshevska, Dimitrinka Jordanova; Sethi, Dinesh; Qirjako, Gentiana; Tozija, Fimka; Jordanova, Tamara
Abstract : Background: Child maltreatment is a serious public health problem that has graved impact on health and well-being of children. The current situation of child maltreatment in Macedonia, Montenegro, Serbia and Albania, aimed to identify the gaps and needs, and take further actions for prevention in line with the recommendations of the European report on preventing child maltreatment and the WHO European child maltreatment prevention action plan 2015–2020. Methods: In the period of November 2014 to October 2015 the situation analysis have been conducted in four respected countries. The analysis relies on: 1) assessments with the relevant stakeholders by semi-structured interviews and 2) computer-based search in the area of: policy framework, legal framework, researches and study data obtained; and surveillance data. Results: Macedonia and Albania has prohibited corporal punishment in all settings, and in Montenegro and Serbia needs to be additionally legalised in home setting, still the prevalence rates of physical violence are high in all countries from 21% in Macedonia up to 40% in Albania. The policy framework targeting child abuse and neglect have been implemented in Macedonia and Serbia covering both protection and prevention. In Montenegro and Albania, the policy has tackled child abuse and neglect in other cross-cutting policy documents. Majority of the services are provided by the protection services and less on implementing evidence based preventing programmes. The heath, social, police, education and justice sectors need coordinated approach in delivering the quality services for recording, detection, treatment, prevention and protection of children. The relevant data suggest persisting of inequalities. Conclusions: Policy and legal frameworks in the countries supports suitable platform for child maltreatment prevention in the respected countries. Still there is a need for comprehensive policy with an emphasis on prevention. Additionally, the legal framework in the countries should enable ban of corporal punishment in all settings and reinforcement. The response should facilitate multisectoral approach and collaboration and tailored programmes, plans that combat social inequalities such as: rural/urban, regional, children living in poverty and families at risk.